Nonlinear problems in accelerator physics : proceedings of the INT workshop on Nonlinear Problems in Accelerator Physics held in Berlin, Germany, 30 March-2 April, 1992 /: proceedings of the INT workshop on Nonlinear Problems in Accelerator Physics held in Berlin, Germany, 30 March-2 April, 1992. (2020) - Berz, Martin
No abstract available